Development of Equipment for Air Decontamination in the Ventilation and Air Conditioning Systems of Public Buildings with the Use of the Photocatalysis and Plasmochemistry Methods - Lobanov , L.; CHALAEV, D. M.; Goncharov , P.; Grabova, T.; Pashchin , M.; Goncharovа O.; Sydorenko , V. (Science and Innovation, 2024)
Introduction. Seasonal waves of SARS outbreaks, including COVID-19, necessitate the development of measures to create health-safe conditions in crowded places. Problem Statement. The existing supply and exhaust systems of the centralized heating, ventilation and air conditioning (HVAC) do not protect against infection, moreover, they serve as a source for the accumulation and spread of pathogenic microorganisms. Finding effective ways to clean the air in places of mass gathering of people as a component of anti-epidemic measures is an urgent task. Purpose. The purpose of this research is to develop and create equipment for cleaning and disinfecting air from airborne pathogenic microflora in the HVAC systems, which can be installed in the centralized ventilation systems of buildings without their reconstruction and modifications in technological parameters. Material and Methods. A complex of physical and chemical methods, which includes analytical and experimental techniques with the use of the theory of electrogas dynamics of dispersed systems and the raster scanning microscopy methods, and the methods for comparing the same quality indicators of specimens and initial samples have been used. Results. To study the efficiency of both the individual plasma-chemical and photocatalytic modules, as well as the equipment as a whole under the operating conditions that simulate those of the centralized ventilation system, an experimental stand has been created. The optimal technological parameters of the processes for raising the efficiency of air disinfection and purification in the HVAC systems by the plasma photocatalysis methods have been determined. Technical solutions for increasing the energy efficiency of the experimental stand for the complex air purification and disinfection from a wide class of air pollutants in the supply and exhaust ventilation systems of buildings have been proposed.ent, as well as to determine the required level of innovation factor by maximizing the hidden innovation capacity. Conclusions. Air disinfection by the method of combined plasma-photocatalytic effect on the air flow with a system for catalytic-thermal decomposition of excess ozone ensures effectively removing pollutants and allows reducing the microbiological contamination of the air to a safe level.